The Inn at Tansy Falls - Woods, Cate (Forever, 2022)
Dearest Nell, if you're reading this letter, I'm already gone ... You're my best friend in the world, and as my last request I'm asking you to lay me to rest hundreds of miles away, in my crazy gorgeous, totally one-of-a-kind hometown of Tansy Falls. I know you're a born-and-bred city girl, but hear me out. After first losing Adrian, and then me ... I know your heart is hurting, Nell. I think you'll find that you need Tansy Falls as much as I do. So, I've got it all planned out. For two weeks, you'll be staying at the sweet, local inn and every day you'll be trying something new. And if you follow my instructions to the letter, you may discover there's more to my story than you think. A surprise something ... or someone at the end of it? Only you can find out! Some last advice before you set off, Nell. Don't forget your sturdy boots and make sure to give Boomer, the inn's resident dog, a belly rub from me. Stay well away from former quarterback Brody Knott (boy, do I have some stories about him!). And finally, let the future bring what it brings. While Tansy Falls may look small, I know better than anyone that new beginnings can be found in all kinds of places. That little Vermont town you'd never heard of? Well, it might suddenly begin to feel just like coming home ...